Responses of the microbial community and the production of extracellular polymeric substances to sulfamethazine shocks in a novel two-stage biological contact oxidation system - Zhou, Jia; Chen, Tian; Cui, Jing; Chen, Yan; Zhao, Shuai; Qu, Jian-Hang; Wang, Zitong; Pan, Jingshi; Fan, Lixin (Frontiers in Microbiology, 2023)
Biological contact oxidation reactor is an effective technology for the treatment of antibiotic wastewater, but there has been little research investigating its performance on the sulfamethazine wastewater treatment. In this study, a novel two-stage biological contact oxidation reactor was used for the first time to explore the impact of sulfamethazine (SMZ) on the performance, microbial community, extracellular polymeric substances (EPS) and antibiotic-resistant genes (ARGs). The chemical oxygen demand (COD) and ammonia nitrogen (NH4 + -N) removal efficiencies kept stable at 86.93% and 83.97% with 0.1-1 mg/L SMZ addition and were inhibited at 3 mg/L SMZ. The presence of SMZ could affect the production and chemical composition of EPS in the biofilm, especially for the pronounced increase in T B-P N yield in response against the threat of SMZ. Metagenomics sequencin g demonstrated that SMZ could impact on the microbial community, a high abundance of Candi datus_Promineofilum, unclassi fied_c__Anaerolineae and unclassi fied_c__Betaproteobacteria were positively correlate to SMZ, especially for Candi datus_Promineofilum. Furthermore, Candidatus_Promineofilum not only had the ability of EP S secretion, but also was significantly associated with the primary SMZ resistance genes of sul1 and sul2, which developed resistance against SMZ pressure through the mechanism of targeted gene changes, which provided a useful and easyimplement technology for sulfamethazine wastewater treatment.